Measures to develop 5–6-year-old preschool children’s ability to use sentences for communicative purposes: A situational survey and pedagogical experiment - Lan, Do Thi; Nga, Le Phuong; Hang, Vu Thu; Khuong, Nguyen Duc (Edelweiss Applied Science and Technology, 2026)
This study aims to develop and evaluate a set of pedagogical measures to enhance 5–6-year-old preschool children’s ability to use sentences according to communicative purposes from a communicative-oriented perspective. The research employs a mixed-methods design following a sequential explanatory approach, including a situational survey and a controlled pedagogical experiment. The survey was conducted with teachers and children in several preschools to examine teachers’ awareness, the organization of language activities, and children’s use of sentence types. Based on these findings, targeted measures were designed and implemented in an intervention with experimental and control groups of equivalent initial ability. The results show that children in the experimental group demonstrated significant improvement in using sentences for communicative purposes compared to the control group. The proportion of children below expectations decreased, while those exceeding expectations increased across all sentence types, particularly in imperative and exclamatory forms. These findings confirm the effectiveness of a communicative-pragmatic approach to early language education. Practically, the study suggests that organizing purposeful communicative activities is essential for fostering young children’s verbal communicative competence.